Effect of the CYP4F2 gene on warfarin dose in anticoagulated peruvian patients, 2019-2022 - Oscanoa, Teodoro J. (2024)
Introduction: Warfarin is an anticoagulant whose efficacy depends on reaching and maintaining an INR (International Normalized Ratio) within therapeutic ranges. Up to 60% of interindividual dose-response variability can be explained by pharmacogenes, in this regard there are no studies in Peru. We studied the effect of the CYP4F2 gene on the dose of warfarin in Peruvian patients. Material and Methods: A descriptive and ambispective observational study was carried out with patients seen in the Grau ESSALUD Hospital Hematology Service, Lima, Peru, selected by non-probabilistic convenience sampling. The inclusion criteria were patients anticoagulated for more than three months and with stable doses of warfarin (same dose for at least three outpatient visits and with an INR in therapeutic ranges of 2.5-3.5). Analysis of the CYP4F2 gene was performed by taking a DNA sample from peripheral blood. Results: 70 patients with a mean age of 69.6 + 13.4, male 38 (54.39%) and female 32 (45.7%) entered the study. The mean dose of warfarin was 31.6 + 15.2 mg/week. The genotypic frequency of the CYP4F2 gene, rs2108622 variant (CT) was 55 (78%), 13 (19%) and 2 (3%) of CC, CT, TT, respectively. No deviation from the Hardy-Weinberg equilibrium was found in the variants studied (p=0.56). Mean warfarin doses/week of the CC, CT, TT genotypes were 30.34 + 11.98; 36.4 + 25.6 and 36.25 + 1.8 mg/week, respectively (p=0.397). Conclusion: In conclusion, it appears that CYP4F2 gene genotypes do not have a significant effect on warfarin dose.